A Bivariate Weibull Family with Applications. Issue 2 (3rd April 2017) - John, Preethi; Sankaran, P. G.
SYNOPTIC ABSTRACT: In reliability theory, Weibull distribution is extensively employed for modelling lifetime data and is considered as a versatile family of life distributions. In this article, we derive a family of bivariate Weibull distributions and study its properties. The general form of the copula is Archimedean, which is popularly used in empirical modeling. The dependency structure of the family is investigated. Finally, the family of distributions is applied to two real life data sets.